A strong sustainability approach to development trajectories - Antoine Godin; Anda David; Oskar Lecuyer; Stéphanie Leyronas (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2022)
Sustainable development trajectories are at the heart of many policy debates: CDN and Net Zero trajectories, just transition, climate justice, biodiversity inclusion, etc. These trajectories mostly propose a nexus approach combining climate, ecological, social, technological, economic, and political aspects. In this paper, the authors propose a suite of three guiding principles, inspired by a strong sustainability approach, to construct sustainable trajectories: (i) the a priori refutation of substitutability; (ii) the need to construct multidimensional diagnostics and analyses highlighting synergies and tensions between different indicators; and (iii) the recognition of the importance of building a social construct on the desirable 'good condition' and on the trajectories to reach it. They then show how these principles can be applied in different disciplines and help policymakers in constructing development trajectories.
Keywords: 330; sustainable development; development trajectories; strong sustainabilityQ01; O20; Q57